Molecular mechanisms of metabolic dysregulation in diabetic cardiomyopathy - Zeng, Yue; Li, Yilang; Jiang, Wenyue; Hou, Ning (Frontiers in Cardiovascular Medicine, 2024)
Diabetic cardiomyopathy (DCM), one of the most serious complications of diabetes mellitus, has become recognized as a cardiometabolic disease. In normoxic conditions, the majority of the ATP production (>95%) required for heart beating comes from mitochondrial oxidative phosphorylation of fatty acids (FAs) and glucose, with the remaining portion coming from a variety of sources, including fructose, lactate, ketone bodies (KB) and branched chain amino acids (BCAA).Increased FA intake and decreased utilization of glucose and lactic acid were observed in the diabetic hearts of animal models and diabetic patients. Moreover, the polyol pathway is activated, and fructose metabolism is enhanced. The use of ketones as energy sources in human diabetic hearts also increases significantly. Furthermore, elevated BCAA levels and impaired BCAA metabolism were observed in the hearts of diabetic mice and patients. The shift in energy substrate preference in diabetic hearts results in increased oxygen consumption and impaired oxidative phosphorylation, leading to diabetic cardiomyopathy. However, the precise mechanisms by which impaired myocardial metabolic alterations result in diabetes mellitus cardiac disease are not fully understood. Therefore, this review focuses on the molecular mechanisms involved in alterations of myocardial energy metabolism. It not only adds more molecular targets for the diagnosis and treatment, but also provides an experimental foundation for screening novel therapeutic agents for diabetic cardiomyopathy.